Expression of the L-type calcium channel with two different β subunits and its modulation by Ro 40-5967 - Welling, Andrea; Lacinova, Lubica; Donatin, Kirsten; Ludwig, Andreas; Bossert, Eva-Maria; Flockerzi, Veit; Hofmann, Franz (Pflügers Archiv, 1995)
The smooth muscle α1Cb subunit of the L-type calcium channel was expressed alone (CHOα1 cell) or together with the skeletal β1 (CHOαβ1 cell) subunit or smooth muscle β3 (CHOα1β3 cell) subunit in Chinese hamster ovary (CHO) cells. The interaction of the expressed calcium channels with the non-dihydropyridine calcium channel blocker Ro 40-5967 was studied. Ro 40-5967 decreased isradipine binding by an apparent allosteric interaction and blocked the barium inward currents (IBa) in a voltage- and use-dependent manner in all cells. The steady-state inactivation curves were shifted to hyperpolarizing potentials in the presence of Ro 40-5967. The rate of channel inactivation was increased in CHOα1 and CHOα1β3 cells. The shift in the steadystate inactivation curve and the increase in channel inactivation were less pronounced in CHOα1β1 cells than in the other cell lines. Low concentrations of Ro 40-5967 increased IBa by up to 198% in 33% of the CHOα1β1 cells. In addition, higher concentrations of Ro 40-5967 were required to inhibit IBa in 60% of the CHOα1β3 cells. These results suggest that the β subunits modify the interaction of the non-dihydropyridine Ro 40-5967 with the expressed calcium channel α1 subunit.